The structure of value as a social phenomenon - Reutsky, Alexander S. (Journal of the Belarusian State University. Philosophy and Psychology, 2026)
The study of values is a complex and comprehensive issue that touches on a wide range of human life. The very concept of value, due to its fluidity and wide variety of interpretations, differs across cultures and societies. Furthermore, the values of younger generations conflict with those of older generations. Given the changing form and content of today’s values, there is a need to study them as a three-part unit.